Ultrasound-assisted extraction (UAE) of phenolic compounds from Brosimum alicastrum fruit and their antioxidant capacity - Aguilar-Piloto, Gustavo; Negrón-Diaz, Andrea Carolina; Moo-Huchin, Victor Manuel; Ramírez-Sucre, Manuel Octavio; Delgadillo-Díaz, Mariana; Cuevas-Glory, Luis Fernando; Sauri-Duch, Enrique (Ecosistemas y Recursos Agropecuarios, 2023)
The aim of this work was to compare the effect of solvents in the UAE on the content of total phenolic compounds (TPC) and in vitro antioxidant capacity DPPH and reducing power (RP) of the whole fruit B. alicastrum. The phenolic compounds of the freeze-dried fruit were extracted in an ultrasonic bath for 30 min at 30 °C, 100 % amplitude and 40 kHz frequency. The solvents used were: ethanol (Et-OH), methanol (Met-OH), 50 % ethanol (50 % Et-OH) and 50 % methanol (50 % Met-OH). The UAE of phenolic compounds of the fruit was improved by adding distilled water to the organic solvent. The highest TPC content and antioxidant capacity were obtained with 50 % Met-OH. There was a high positive correlation between TPC and antioxidant capacity (DPPH and PR). It is suggested to use 50 % Met-OH as solvent for UAE of phenolic compounds of fruit B. alicastrum.